PENERAPAN FAKTOR-FAKTOR YANG MEMPENGARUHI LEMAHNYA MINAT MAHASISWA TERHADAP SASTRA DAN BUDAYA DI CIANJUR - Yuli sri astuti; Librilianti Kurnia Yuki (Universitas Warmadewa, 2023)
This study aims to analyze the application of factors that influence the weakness of student interest in literature and culture in Cianjur. This method used in this research is qualitative. This data was obtained from the respondents of Universitas Putra Indonesia students by distributing questionnaires through Google forms. The results of this study indicate that there are 4 literary factors that influence the weakness of student interest in literature and culture in Cianjur. Among them are: 1). One's thinking power, 2). A person's residence, 3). Limited economic factors, 4). The means of one's heart. In addition, there are 9 cultural factors, including: 1). Environmental factors, 2). Technological development factors, 3). Inadequate facilities factor, 4). Race factor, 5). Factors of relations between nations, 6). Social factors, 7). Religious factors, 8). Fashion factor, 9). prestige factor. This study aims to determine the factors that influence the weakness of student interest in literature and culture in Cianjur. Keywords: Literature, Cultural Pillars